Computer networking : a top-down approach - Kurose, James F.; Ross, Keith W., 1956- (Noida : Pearson, 2022)
"Welcome to the eighth edition of Computer Networking: A Top-Down Approach. Since the publication of the first edition 16 years ago, our book has been adopted for use at many hundreds of colleges and universities, translated into 14 languages, and used by over one hundred thousand students and practitioners worldwide. We ve heard from many of these readers and have been overwhelmed by the positive response"--
First Impression : 2022, Nineth Impression : 2025, Tenth Impression.
Indian subcontinent adaptation.
Includes bibliographical references and index.
CSE
Keywords: Internet; Computer networks; Computer science